2021
DOI: 10.1016/j.ijnurstu.2021.103921
|View full text |Cite
|
Sign up to set email alerts
|

How long do nursing staff take to measure and record patients’ vital signs observations in hospital? A time-and-motion study

Abstract: Introduction Monitoring vital signs in hospital is an important part of safe patient care. However, there are no robust estimates of the workload it generates for nursing staff. This makes it difficult to plan adequate staffing to ensure current monitoring protocols can be delivered. Objective To estimate the time taken to measure and record one set of patient's vital signs; and to identify factors associated with the time required to measure and record one set of patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…It also improves workers' working conditions and the environment by preventing unnecessary manpower movement [ 1 ]. There is a strong need to discuss and apply time-motion studies (TMSs) to improve the working efficiency in healthcare [ 2 ]. By considering this need an attempt is made to collect the available data on TMSs by searching different research papers through different sources.…”
Section: Introductionmentioning
confidence: 99%
“…It also improves workers' working conditions and the environment by preventing unnecessary manpower movement [ 1 ]. There is a strong need to discuss and apply time-motion studies (TMSs) to improve the working efficiency in healthcare [ 2 ]. By considering this need an attempt is made to collect the available data on TMSs by searching different research papers through different sources.…”
Section: Introductionmentioning
confidence: 99%
“…18 A ROX <=10 predicted 28day mortality in patients with sepsis, 3 and Prower et al found that a ROX value of 14.91 identified deterioration four hours earlier than NEWS2. 4 Unlike early warning scores, which require a complete set of vital signs that take time to measure and calculate, 19 the ROX index only requires an oximeter and can be quickly and repeatedly determined. Therefore, ROX may be particularly valuable in low-resource settings and for frequently monitoring post-operative patients; levels falling below 22 causing increasing concern.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Over the 4 years of the study, total observations recorded increased by 14% from 1 976 872 to 2 249 118 as shown in table 3 below, with median observations per patient per day rising from 3 to 4 (online supplemental figure 2). If time taken to record observations is assumed to be 3 min 45 s, 7 this equates to an increase of 85 000 minutes a month. Sixty-five per cent of observations were attributable to patients under medical specialties, 34% to patients under surgical specialties and 1% to patients discharged by the emergency department.…”
Section: Observations and Early Warning Scoresmentioning
confidence: 99%